Problematika Teknologi dalam Pendekatan Deep Learning Matematis di Indonesia - Mudjib, Ridho; Wastralangkara, Wailah Wajra; Anne Aulia Syalsabilla; Wati Susilawati (Papanda, 2025)
Mathematics learning is not sufficient by relying solely on memorization; it also requires deep conceptual understanding and active student engagement. The deep learning approach has emerged as a more meaningful alternative, with educational technology playing a crucial role in supporting its implementation. This study employs a Systematic Literature Review (SLR) method using the PRISMA protocol, which includes several stages: identification, screening, eligibility testing, and final selection. The PICOC framework was applied to ensure appropriate inclusion criteria. From 60 articles initially identified across databases such as Google Scholar, Garuda, DOAJ, and SINTA, 30 articles were found to meet the requirements for analysis. The findings reveal that the most frequently integrated technologies in mathematics learning include GeoGebra, learning management systems such as Google Classroom and Moodle, augmented reality, e-modules, mobile applications, and artificial intelligence–based media. These technologies have been shown to enhance students’ understanding of mathematical concepts, strengthen critical thinking skills, and foster motivation as well as independent learning. Nevertheless, the implementation of technology in mathematics education in Indonesia continues to face significant challenges, including limited infrastructure, low levels of teachers’ digital literacy, unequal access across regions, and insufficient training and policy support. The analysis also highlights that most existing studies remain descriptive and product-oriented, while conceptual research on the integration of deep learning and technology within the local context is still scarce. This study concludes that more comprehensive strategies are required, such as strengthening teacher capacity, developing technology-responsive curricula, and building an inclusive digital ecosystem, in order to make mathematics learning in Indonesia more effective and sustainable